Polishing methods of an alumina-reinforced feldspar ceramic - Bottino, Marco Cícero; Valandro, Luiz Felipe; Kantorski, Karla Zanini [UNESP]; Bressiani, José Carlos; Bottino, Marco Antonio [UNESP] (FapUNIFESP (SciELO), 2006)
The purpose of this study was to test the hypothesis that mechanical polishing methods of ceramic surfaces allow similar superficial roughness to that of glazed surfaces. Twenty-five Vitadur Alpha ceramic discs (5 mm x 2 mm) were prepared according to the manufacturer's specifications. All specimens were glazed and randomly assigned to 5 groups (n=5), according to finishing and polishing protocols: G1: glazed (control); G2: diamond bur finishing; G3: G2 + silicon rubber tip polishing; G4: G3 + felt disc/diamond polishing paste; G5: G3 + felt disc impregnated with fine-particle diamond paste. Next, surface roughness means (Ra - μm) were calculated. Qualitative analysis was made by scanning electron microscopy. Surface roughness data were submitted to ANOVA and Tukey's test at 5% significance level. G1 and G4 were statistically similar (p>0.05). G2 presented the highest roughness means (p<0.05) followed by groups G3, G5, G4 and G1 in a decreasing order. The hypothesis was partially confirmed as only the mechanical polishing (G4) produced similar superficial roughness to that of surface glazing, although finishing and polishing are technically critical procedures.
Keywords: Alumina-reinforced feldspar ceramic; Finishing and polishing; Surface roughness; aluminum oxide; aluminum silicate; diamond; feldspar; potassium derivative; silastic; unclassified drug; vitadur alpha; ceramics; chemistry; clinical trial; controlled clinical trial; controlled study; human; instrumentation; materials testing; methodology; randomized controlled trial; scanning electron microscopy; surface property; tooth brushing; tooth prosthesis; Aluminum Oxide; Aluminum Silicates; Ceramics; Dental Polishing; Dental Porcelain; Diamond; Humans; Materials Testing; Microscopy, Electron, Scanning; Potassium Compounds; Silicone Elastomers; Surface Properties